Energy, water and food security through a waste-driven polygeneration system for sustainable dairy production. (15th January 2022) - Luqman, Muhammad; Al-Ansari, Tareq
Abstract: Ensuring secure and sustainable food production amidst growing demand requires developing high-yield sustainable food production systems, noting that conventional food production systems are large consumers of energy and water resources. Moreover, they induce substantial environmental impacts. In this context, this study considers dairy food production systems, and proposes a dairy waste driven polygeneration system that can increase the milk yield of the dairy food production system whilst reducing its environmental impact. The system utilises dairy manure, very low concentration methane, wastewater, and harsh environmental conditions in an integrated manner to fulfil the dairy farms' vital needs, including air-conditioning, electricity, and freshwater. In addition, the system also provides a solution concerning social perception related to wastewater reuse for potable purposes in the form of an integrated electrolyser and fuel-cell cycle. Unique to this study is the harnessing of the energy of the methane, which is in very low concentrations in the barns, and benefitting from the harsh environmental conditions in an integrated manner. Comprehensive thermodynamic investigations revealed that the system generates 2.17 MW of Electricity, 1152 m 3 of freshwater daily, 6970 tons of cooling capacity, and 1.6 kg/day of H2 . Besides, on a daily basis, the system consumes 864 tons of manure, recycles 732.5 m 3 of wastewater, and utilises 87.62 tons of methane (resulting in savings of ∼711, 750 tons of CO2 eq. annually). The calculated energy and exergy efficiencies of the polygeneration system are 50% and 4%, respectively. Moreover, in the design of polygeneration systems, the importance of the proper definition of the thermodynamic system's boundaries and the effects of technology choice for the same purpose is illustrated. Furthermore, the parametric investigations revealed that the system performs stable with variations in the inputs and ambient conditions. Also, unlike other systems, the system's performance improves in harsher environmental conditions. This study also illustrates that the food production systems can be developed for decentralised operations with near zero-waste outputs and near-zero emissions. Graphical abstract: Image 1 Highlights: A sustainable solution towards zero-waste food production systems (dairy farming). Integrated utilization of all the wastes and fulfilment of essential needs of dairy farms. Very-low concentration methane is utilized in a novel integrated manner. A hydrogen energy-based solution for social perceptions in wastewater reuse is proposed. The system's performance improves at hotter and/or more humid climates.